A new cutthroat eel of the genus Synaphobranchus (Anguilliformes: Synaphobranchidae) from Taiwan - Ho, Hsuan-Ching; Hong, Wei-Chun; Chen, Hong-Ming (Zootaxa, 2018)
A new species of the cutthroat eel genus Synaphobranchus is described from Taiwan on the basis of 12 types and 11 non-type specimens. The new species can be distinguished from its congeners in having most of its head and abdomen naked, except for a patch of scales behind the eye, dorsal surface of trunk naked or covered by scattered scales; scales oval in shape; dorsal fin slightly before to about opposite to origin of anal fin; mean vertebral formula 28-28-131, precaudal vertebrae 50–56, total vertebrae 124–135. Comments of the congeners occurred in adjacent regions are provided.